INTEGRASI PENDIDIKAN AGAMA ISLAM DAN IPS DALAM PEMBENTUKAN KARAKTER SISWA DI SMP NEGERI 3 TANJUNG PURA - Karnedi, Sukri; Pasaribu, Munawir (CV. Lafadz Jaya, 2025)
This study aims to examine the integration of Islamic Religious Education (IRE) and Social Studies (SS) in shaping students' character at SMP Negeri 3 Tanjung Pura. The research method used is qualitative with a phenomenological model and a field research approach. The research population consists of IRE teachers, SS teachers, and students at SMP Negeri 3 Tanjung Pura. The results of the study indicate that the integration of the two subjects successfully enhances student character through the connection of subject material with Islamic values, the use of integrated learning methods, and practical activities that involve students in social contexts.